Associations between Thyroid Hormones, Calcification Inhibitor Levels and Vascular Calcification in End-Stage Renal Disease - Meuwese, Christiaan Lucas (PLoS One, 2015)
INTRODUCTION: Vascular calcification is a common, serious and elusive complication of end-stage renal disease (ESRD). As a pro-calcifying risk factor, non-thyroidal illness may promote vascular calcification through a systemic lowering of vascular calcification inhibitors such as matrix-gla protein (MGP) and Klotho. METHODS AND MATERIAL: In 97 ESRD patients eligible for living donor kidney transplantation, blood levels of thyroid hormones (fT3, fT4 and TSH), total uncarboxylated MGP (t-ucMGP), desphospho-uncarboxylated MGP (dp-ucMGP), descarboxyprothrombin (PIVKA-II), and soluble Klotho (sKlotho) were measured. The degree of coronary calcification and arterial stiffness were assessed by means of cardiac CT-scans and applanation tonometry, respectively. RESULTS: fT3 levels were inversely associated with coronary artery calcification (CAC) scores and measures of arterial stiffness, and positively with dp-ucMGP and sKlotho concentrations. Subfractions of MGP, PIVKA-II and sKlotho did not associate with CAC scores and arterial stiffness. fT4 and TSH levels were both inversely associated with CAC scores, but not with arterial stiffness. DISCUSSION: The positive associations between fT3 and dp-ucMGP and sKlotho suggest that synthesis of MGP and Klotho is influenced by thyroid hormones, and supports a link between non-thyroidal illness and alterations in calcification inhibitor levels. However, the absence of an association between serum calcification inhibitor levels and coronary calcification/arterial stiffness and the fact that MGP and Klotho undergo post-translational modifications underscore the complexity of this association. Further studies, measuring total levels of MGP and membrane bound Klotho, should examine this proposed pathway in further detail.